Microwave Assisted Synthesis and Biological Studies of Novel Mannich Bases - Abdul Jameel, A.; Syed Ali Padusha, M. (Asian Journal of Chemistry, 2010)
In this work, microwave irradiation was employed for the synthesis of Mannich bases using piperidin-4-one, heteroaldehyde and amide moieties. The structures of compounds were characterized through analytical (elemental analysis, melting point and TLC) and spectral methods (IR, 1H NMR, 13C NMR and Mass). Further the compounds were screened for the antibacterial and antifungal activities.